International standard measures during the AGBRESA bed rest study. (November 2022) - Clément, Gilles R.; Crucian, Brian E.; Downs, Meghan; Krieger, Stephanie; Laurie, Steve S.; Lee, Stuart M.C.; Macias, Brandon R.; Mulder, Edwin; Rivas, Eric; Roma, Peter G.; Rosenberg, Marissa J.; Sibonga, Jean D.; et al.
Abstract: The Artificial Gravity Bed Rest with European Space Agency (AGBRESA) study involved 2 campaigns of 60-day bed rest at 6° head down tilt in the:envihab facility in Cologne, Germany, in 2019. The objective was to determine whether centrifugation of supine subjects mitigates physiological changes that occur due to the exposure to the spaceflight analog of 6° head down tilt. A set of international standard measures was used to evaluate bone, muscle, nutritional status, ocular changes, and psychological state and to assess cardiovascular, sensorimotor, and immune systems functions. After 60 days of bed rest, the subjects who were not exposed to centrifugation had significant decreases in mineral density at the hip and lumbar spine, decreased muscle strength of the knee and ankle, reduced maximal aerobic capacity, orthostatic intolerance, and impaired balance and locomotion, as well as significant biochemical, immunological, and psychological alterations. A daily 30-min exposure to 1 Gz supine centrifugation at the center of mass (0.3 Gz at the head, 2 Gz at the feet) mitigated mineral density loss in the femur neck and lumbar spine; and lessened the effects of bed rest on aerobic capacity, biochemistry, and immunology. However, low statistical power could contribute to the non-significant effects that are reported. Highlights: 60-day bed rest induces decreased bone loss, muscle strength and aerobic capacity. Bed rest also affects vascular, balance, immune, ocular, and psychology functions. Daily 30-min of centrifugation mitigates biochemical and immunological alterations. Centrifugation also mitigates bone loss and decreased aerobic capacity.